Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1038/nsmb.2599
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular determinants of nucleosome retention at CpG-rich sequences in mouse spermatozoa

Abstract: In mammals, fusion of two morphologically distinct gametes, oocytes and spermatozoa, leads to the formation of totipotent embryos. Acquisition of totipotency is thought to be mediated by extensive epigenetic reprogramming of parental genomes, affecting DNA methylation and histone modifications, and possibly replication timing and transcriptional activity in parental specific manners [1][2][3][4] . It is currently unclear to what extent differential reprogramming of maternal and paternal genomes is due to diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
379
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(428 citation statements)
references
References 53 publications
(54 reference statements)
31
379
1
Order By: Relevance
“…3B,D), as was previously reported. 16,19 Overall, we observed a higher normalized read density at protein-coding promoter regions in HFD (HFD7) compared to LFD (LFD8), consistent with the results of the peak analysis.…”
Section: H3 Retention In Spermatozoasupporting
confidence: 84%
See 2 more Smart Citations
“…3B,D), as was previously reported. 16,19 Overall, we observed a higher normalized read density at protein-coding promoter regions in HFD (HFD7) compared to LFD (LFD8), consistent with the results of the peak analysis.…”
Section: H3 Retention In Spermatozoasupporting
confidence: 84%
“…Although most of the histone proteins are replaced by protamines during spermatogenesis, several recent reports suggest that a portion of the haploid genome is retained in nucleosomes, [16][17][18][19][20] with about 1-4% being retained in the murine genome. To address the effect of diet on sperm histone content, we performed chromatin immunoprecipitation (ChIP) using specific antibodies against histone H3.…”
Section: H3 Retention In Spermatozoamentioning
confidence: 99%
See 1 more Smart Citation
“…The first high-resolution genome-wide map of human spermatozoa histones shows a strong enrichment in methylated histone H3K4me3 at many promoters of developmental genes, genes encoding signaling factors, imprinted gene clusters, microRNA and HOX gene clusters (17). These studies showed that the promoters in sperm are enriched in H3K4me3 and H3K27me3, and it was suggested that genes with these marks play a particularly important role in epigenetic inheritance (1618). On the other hand, more recent nucleosome mapping studies showed that sperm nucleosome fraction is enriched in gene-poor regions and is generally depleted from the promoters (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Nucleosomes in sperm are also enriched in CpG islands (18). Recently, a strong association between nucleosome retention at CpG islands in sperm and the establishment of unmethylated regions in the early mammalian embryo was shown (28).…”
Section: Introductionmentioning
confidence: 99%